Microplastic contamination in processed and unprocessed sea salts from a developing country and potential risk assessment. (December 2022) - Ujjaman Nur, As-Ad; Hossain, M. Belal; Banik, Partho; Choudhury, Tasrina Rabia; Liba, Samia Islam; Umamaheswari, S.; Albeshr, Mohammed Fahad; Senapathi, Venkatramanan; Arai, Takaomi; Yu, Jimmy
Abstract: In aquatic environments, microplastics (MPs) are pervasive which could have a considerable negative impact on the environment, organisms and pose a risk to human health. However, knowledge about the exposure and ecological risk of MPs in the coastal ecosystems of developing countries is limited. In this study, we analyzed salt samples from five commonly consumed processed and unprocessed sea salts of different commercial brands originated from 15 salt pans in Bangladesh to assess the abundance, characteristics and potential risks of MPs. The quantities of MPs in unprocessed salts (average 195 ± 56 item/kg) were higher than those in the processed salts (average 157 ± 34 item/kg). One-way analysis of variance (ANOVA) showed significant (p < 0.05) differences among the average numbers of MPs in both processed and unprocessed salts. MP levels in this study were 2–3 times higher than those reported from some other countries. Fiber-shaped and transparent MPs were dominant in both cases. MPs less than 0.5 mm in size were the most abundant in both unprocessed (58.2%) and processed (62.2%) salts. Fourier-transform infrared spectroscopy (FTIR) analysis confirmed five types of polymers, including polyethylene terephthalate (PET−35%), polypropylene (PP−27.5%), polyethylene (PE−25%), polystyrene (PS−10%), and Nylon (2.5%) in the studied salts. The sea salts were classified as potential hazard index (PHI) levels IV to V, indicating serious MP contamination, whereas potential ecological risk factor (Ei ), potential ecological risk index (RI), and pollutant load index (PLI) indicated moderate levels of pollution of MPs. Domestic and municipal wastewater effluents to Bay of Bengal and fishing activities may attributed to presence of MPs in the sea salt. These findings can be used by consumers, salt industries and policy makers to reduce MPs levels during consumption, production and policymaking. Graphical abstract: Image 1 Highlights: First risk assessment of microplastics (MPs) in food-grade sea salt from the study area. The average MPs in unprocessed and processed sea salt were 194.67 ±55.68 item/kg and 157.00 ±34.10 item/kg, respectively. Fibers were mostly dominant in both unprocessed (79.24%) and processed (94.93%) sea salt samples. FTIR confirmed that PET, PP, PE, PS and nylon polymers were present in processed sea salt. Based on PHI values, the risk of MP pollution in Bangladeshi processed sea salt was classified as Hazard category IV to V.